Beginning Reading Instruction for Students at Risk for Reading Disabilities: What, How, and When - Coyne, Michael D.; Zipoli, Richard P.; Ruby, Maureen F. (Intervention in School and Clinic, 2006)
In this article, the authors assist teachers who are working with young students at risk for reading disabilities by helping make sense of the large—but unwieldy—scientific knowledge base. They offer a conceptual framework for thinking about beginning reading instruction and intervention across three dimensions: the content of instruction (what to teach), the delivery of instruction (how to teach), and the timing of instruction (when to teach). The authors discuss each of these dimensions and describe how teachers can use them to help organize and make sense of what we know about beginning reading instruction for students experiencing reading difficulties.
Keywords: dept.cmd; peer-reviewed

Direct Vocabulary Instruction in Kindergarten: Teaching for Breadth versus Depth - Coyne, Michael D.; McCoach, D. Betsy; Loftus, Susan; Zipoli, Richard; Kapp, Sharon (The Elementary School Journal, 2009)
Abstract The purpose of this study was to compare 2 methods for directly teaching word meanings to kindergarten students within storybook read‐alouds that varied in instructional time and depth of instruction along with a control condition that provided students with incidental exposure to target words. Embedded instruction introduces target word meanings during storybook readings in a time‐efficient manner. Extended instruction is more time intensive but provides multiple opportunities to interact with target words outside the context of the story. Participants included 42 kindergarten students who were taught 9 target words, 3 with each method. Target words were counterbalanced in a within‐subjects design. Findings indicated that extended instruction resulted in more full and refined word knowledge, while embedded instruction resulted in partial knowledge of target vocabulary. Implications are discussed in relation to the strengths and limitations of different approaches to direct vocabulary instruction in kindergarten and the trade‐offs between instruction that focuses on teaching for breadth versus depth.
Keywords: dept.cmd; peer-reviewed

Direct Instruction of Comprehension: Instructional Examples From Intervention Research on Listening and Reading Comprehension - Coyne, Michael D.; Zipoli Jr., Richard P.; Chard, David J.; Faggella-Luby, Michael; Ruby, Maureen; Santoro, Lana E.; Baker, Scott (Reading & Writing Quarterly, 2009)
This article examines the role of direct instruction in promoting listening and reading comprehension. Instructional examples from 2 programs of intervention research focused on improving comprehension; the Story Read Aloud Program and the Embedded Story Structure Routine are used to illustrate principles of direct instruction. An analysis of these 2 approaches suggests that direct instruction principles are effective in supporting students with varied achievement levels and that these principles can be used to enhance comprehension among students at very different points in reading development. These evidence-based approaches also illustrate that direct instruction can be designed to support complex learning and the development of higher order cognitive strategies.
_eprint: https://doi.org/10.1080/10573560802683697
Keywords: dept.cmd; peer-reviewed

Fiberoptic Endoscopic Evaluation of Swallowing (FEES) with and without Blue-Dyed Food - Leder, Steven B.; Acton, Lynn M.; Lisitano, Heather L.; Murray, Joseph T. (Dysphagia, 2005)
The purpose of this prospective study was to determine if fiberoptic endoscopic evaluation of swallowing (FEES) maintains high intra- and interrater reliability in detecting pharyngeal dysphagia and aspiration without the addition of FD&C Blue No. 1 to food. Twenty consecutive adults referred for a swallow evaluation participated. Nine subjects received blue-dyed food and 11 subjects received regular nondyed food, i.e., yellow pudding and white skim milk. Four variables were rated: (1) the stage transition characterized by depth of bolus flow to at least the vallecula prior to the pharyngeal swallow; (2) evidence of bolus retention in the vallecula or pyriform sinuses after the pharyngeal swallow; (3) laryngeal penetration defined as material in the laryngeal vestibule but not passing below the level of the true vocal folds either before or after the pharyngeal swallow; and (4) tracheal aspiration defined as material below the level of the true vocal folds either before or after the pharyngeal swallow. Three speech–language pathologists experienced in interpreting FEES results independently and blindly reviewed the digitized videotape three times. Intrarater agreements for the four variables with blue-dyed and non-blue-dyed food trials were 100% and monochrome trials ranged from 95% to 100%. Average kappa values for interrater reliability ranged from moderate to excellent agreement (0.61–1.00) for all viewing conditions. Kappa values for blue-dyed trials versus monochrome trials were 0.83 and for non-blue-dyed trials versus monochrome trials were 0.88, indicative of excellent reliability under both viewing conditions. FEES maintains both high intra- and interrater reliability in detecting the critical features of pharyngeal dysphagia and aspiration using either blue-dyed or non-blue-dyed foods. The endoscopist, therefore, can be assured of reliable FEES results using regular, non-dyed food trials.
Keywords: Aspiration; Blue dye; Deglutition; Deglutition disorders; Fiberoptic endoscopic evaluation of swallowing; Pharyngeal dysphagia; dept.cmd; peer-reviewed

Answering Orientation Questions and Following Single-Step Verbal Commands: Effect on Aspiration Status - Leder, Steven B.; Suiter, Debra M.; Lisitano Warner, Heather (Dysphagia, 2009)
In the acute-care setting patients with altered mental status as a result of such diverse etiologies as stroke, traumatic brain injury, degenerative neurologic impairments, dementia, or alcohol/drug abuse are routinely referred for dysphagia testing. A protocol for dysphagia testing was developed that began with verbal stimuli to determine patient orientation status and ability to follow single-step verbal commands. Although unknown, it would be beneficial to ascertain if this information on mental status was predictive of aspiration risk. The purpose of this investigation was to determine if there was a difference in odds for aspiration based upon correctly answering specific orientation questions, i.e., 1. What is your name? 2. Where are you right now? and 3. What year is it?, and following specific single-step verbal commands, i.e., 1. Open your mouth. 2. Stick out your tongue. and 3. Smile. In a consecutive retrospective manner data from 4070 referred patients accrued between 1 December 1999 and 1 January 2007 were analyzed. The odds of liquid aspiration were 31% greater for patients not oriented to person, place, and time (odds ratio [OR] = 1.305, 95% CI = 1.134–1.501). The odds of liquid aspiration (OR = 1.566, 95% CI = 1.307–1.876), puree aspiration (OR = 1.484, 95% CI = 1.202–1.831), and being deemed unsafe for any oral intake (OR = 1.688, 95% CI = 1.387–2.054) were, respectively, 57, 48, and 69% greater for patients unable to follow single-step verbal commands. Being able to answer orientation questions and follow single-step verbal commands provides information on odds of aspiration for liquid and puree food consistencies as well as overall eating status prior todysphagia testing. Knowledge of potential increased odds of aspiration allows for individualization of dysphagia testing thereby optimizing swallowing success.
Keywords: Aspiration; Cognition; Deglutition; Deglutition disorders; peer-reviewed

Comparisons of P300s from Standard Oddball and Omitted Paradigms: Implications to Exogenous/Endogenous Contributions - McCullag, Jennifer; Weihing, Jeffrey; Musiek, Frank (Journal of the American Academy of Audiology, 2009)
Purpose: To compare the amplitude, latency, morphology, and threshold of the auditory P300 using standard oddball and omitted paradigms. Research Design: P300 waveforms were measured from the Cz electrode site. Frequent stimuli for both paradigms were 1000 Hz tone bursts. Target stimuli for the standard oddball paradigm were 2000 Hz tone bursts and an omitted stimulus, or silent gap, for the omitted paradigm. Study Sample: Fifteen bilaterally normal-hearing young adults. Results: There were significantly lower amplitudes, poorer morphology, and higher thresholds for the P300 using an omitted paradigm compared to the standard oddball paradigm. Conclusion: These results suggest that the auditory P300 could have a larger exogenous component than traditionally thought.
Keywords: Key Words Endogenous; P300; dept.cmd; exogenous; intensity effects; omitted paradigm; peer-reviewed

Interdisciplinary Management of Stroke Clients. - Purdy, Mary H. (2006)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Communication Disorders and Persons with Developmental Disabilities. - Cascella, Paul W. (2002)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Clinical efficacy of electrophysiologic measures in APD management programs - Jirsa, R.E. (Seminars in Hearing, 2002)
Determining the relative efficacy of various intervention programs for auditory processing disorders (APD) is a major goal in the field of rehabilitative audiology. Currently, because of their widespread availability, the most commonly used measuring tools to assess the central auditory system have been behaviorally based. Such measures do have notable disadvantages in that they may be influenced by a number of extraneous variables that may impede, or at least influence, efficacy measures. Electrophysiologic measures offer unique advantages not available from the behavioral measures. A significant amount of research has been completed offering compelling evidence relative to the clinical utility of a number of these electrophysiologic measures, including the maximum length sequences-auditory brainstem response, the middle latency response, the obligatory long latency responses, and the MMN and P3 event-related potentials. This article will review the current research related to electrophyiologic measures and present a rationale for including them in the management program.
11 citations (Crossref) [2023-10-31]
Keywords: Clinical efficacy; Electrophysiology; Middle latency response; Mismatch negativity; P3 event-related potential; Speech perception; auditory nervous system; clinical practice; dept.cmd; diagnostic accuracy; diagnostic procedure; electrophysiology; event related potential; evoked auditory response; human; middle latency response; mismatch negativity; perception deafness; review; speech perception

Executive function ability in persons with aphasia - Purdy, M. (Aphasiology, 2002)
Background: There is an increasing recognition that the communication problems one observes in persons with aphasia extend beyond verbal deficits and that the myriad of symptoms observed are not solely due to a faulty linguistic system. Rather, there exists a coalition of causal elements resulting in a wide range of communicative deficits. There is some preliminary evidence suggesting that communicative success of clients with aphasia may depend on the integrity of executive function skills. Executive functions are called into play when an individual is involved in a complex, novel activity. They allow us to plan, sequence, organise, and monitor goal-directed activities in a flexible manner as demanded by situational and environmental changes. When linguistic skills are impaired, individuals need to rely on other cognitive skills in order to communicate. Aims: The purpose of this study was to explore executive functioning ability in persons with aphasia. Methods & procedures: A total of 15 individuals with aphasia and 12 healthy control subjects participated in this study. Three dimensions of performance were examined (accuracy, speed, and efficiency) in the context of neuropsychological tests designed to examine cognitive flexibility and goal-directed planning (Wisconsin Card Sorting Test, Porteus Maze Test, Tower of London, and Tower of Hanoi). Outcomes & results: Results indicated that the two groups performed with similar levels of accuracy on two of the four tests. However, significant differences were found on all speed and efficiency variables, suggesting decreased executive functioning skills in the group of individuals with aphasia. Conclusions: It is important to consider executive functioning ability in clients with aphasia and attempt to determine the influence of executive function skill on communicative performance. Understanding the cognitive abilities as well as the linguistic abilities of these clients may ultimately help clinicians determine which patients are better candidates for intervention as well as which treatment approaches would be most efficient and beneficial.
108 citations (Crossref) [2023-10-31]
Keywords: Wisconsin card sorting test; accuracy; adult; aged; aphasia; article; clinical article; cognition; communication disorder; comparative study; controlled study; dept.cmd; human; interpersonal communication; language ability; linguistics; maze test; mental function; mental performance; neuropsychological test; peer-reviewed; planning; skill; treatment planning

Script knowledge following stroke - Purdy, M.H. (Journal of Medical Speech-Language Pathology, 2002)
This study examined script knowledge in 20 subjects who sustained a stroke (10 with left hemisphere brain damage and aphasia and 10 with right hemisphere brain damage) and 10 neurologically normal subjects. Script knowledge was examined via performance on three tasks: procedural sequencing, procedure production, and procedural discourse. Neurologically normal subjects performed all tasks accurately, and all subjects in the stroke group completed at least one of the three tasks for each script accurately, suggesting that script knowledge was preserved in this mildly brain-damaged population. However, significant differences were obtained between the neurologically normal and stroke groups when overall performance was examined. These findings suggest that additional cognitive processes influence task performance. Implications of these findings are discussed.
Keywords: adult; aged; aphasia; article; clinical article; controlled study; dept.cmd; female; human; information processing; language ability; left hemisphere; male; priority journal; right hemisphere; stroke; task performance; ⛔ No DOI found

Communication and its development in autism spectrum disorders - Paul, R. (Autism and Pervasive Developmental Disorders, Second Edition, 2007)
Introduction Communication deficits are one of the core symptoms of autism spectrum disorders (ASDs). People with ASD can be slow to begin talking, or may not learn to talk at all; others may learn to produce words and sentences but have difficulty using them effectively to accomplish social interactive goals. In this chapter we will discuss the course of the development of communication in ASD and will outline how communication deficiencies in this population are identified and treated. Before we do, however, we should be clear about three important terms we will be using, which are illustrated in Figure 4.1. The term “communication” is the broadest of this trio. It refers to all forms of sending and receiving messages, not only with language, but in other ways, such as with gestures, body language, even the way we dress. Animals can also communicate by means of their vocalizations to alert others to danger, for example. That's why the largest circle in Figure 4.1 represents communication. Within the realm of communication, language represents a specific type, so it is enclosed within the larger circle of communication in the figure. Language involves the creation of a potentially infinite set of never-before-conveyed messages through the combination of words in rule-governed ways that allow the formation of sentences to express meaning to others. © Cambridge University Press, 2007 and 2009.
Journal Abbreviation: Autism and Pervasive Developmental Disorders, Second Edition
Keywords: dept.cmd

Foreword - Paul, R. (Single-Word Reading: Behavioral and Biological Perspectives, 2007)
Keywords: dept.cmd

Maximum length sequences-auditory brainstem responses from children with auditory processing disorders - Jirsa, R.E. (Journal of the American Academy of Audiology, 2001)
This study was designed to evaluate maximum length sequences-auditory brainstem responses (MLS-ABR) in children with auditory processing disorders and to compare these results with a normal control group matched for age, intelligence, and gender. Although each waveform was analyzed for the presence of waves I, III, and V, the primary focus was wave V. Although absolute latency measures for wave V were obtained from all subjects, waves I and III were not always identified. Although the results showed latency increases for all waveforms in both groups, the only significant difference noted was an increase in wave V latency for both the left and right ears in the clinical group. These results suggest that the MLS-ABR may be useful in the assessment of auditory processing disorders. Implications for the potential use of the MLS-ABR in management programs are discussed.
27 citations (Crossref) [2023-10-31]
Keywords: *Evoked Potentials; Auditory; Brain Stem/ph [Physiology]; *Hearing Disorders/di [Diagnosis]; Adolescent; Auditory brainstem response; Auditory evoked potentials; Auditory processing disorders; Child; Evoked Potentials; Auditory; Brain Stem; Female; Hearing Disorders; Hearing Disorders/ep [Epidemiology]; Hearing Tests; Humans; Male; Maximum length sequences; Random Allocation; Speech Perception; Speech Perception/ph [Physiology]; Time Factors; adolescent; age; article; child; clinical article; comparative study; controlled study; dept.cmd; evoked brain stem auditory response; female; gender; hearing impairment; human; intelligence; latent period; male; medical assessment; peer-reviewed; priority journal; sensory system electrophysiology; waveform

"Putting things in context": Literal and discourse approaches to comprehension assessment - Paul, R. (Seminars in Speech and Language, 2000)
Research on receptive language development in typical children, especially as explicated in a classic paper by Robin Chapman, is reviewed. These findings raise three challenges for clinicians assessing comprehension in children with language disorders: (1) contrary to popular wisdom, comprehension does not always precede production in a simple step-by-step way; (2) comprehension is a private event; indicators of comprehension must be used to assess it, and these indicators can be misleading; and (3) children with subtle comprehension deficits may do well on standardized tests that are not sensitive to their difficulties with real-time discourse. Some strategies for addressing these challenges, as well as a framework for assessing comprehension, are offered.
11 citations (Crossref) [2023-10-31]
Keywords: *Child Language; *Cognition; *Language Tests; *Verbal Behavior; Child Language; Child; Preschool; Cognition; Comprehension assessment; Comprehension deficits; Comprehension stages; Discourse comprehension; Humans; Language Tests; Verbal Behavior; article; cognition; dept.cmd; human; language development; language test; preschool child; verbal behavior

Evidence-based practice among speech-language pathologists: attitudes, utilization, and barriers. - Zipoli, Richard P Jr; Kennedy, Marianne (American Journal of Speech-language Pathology, 2005)
A total of 240 speech-language pathologists responded to a questionnaire examining attitudes toward and use of research and evidence-based practice (EBP). Perceived barriers to EBP were also explored. Positive attitudes toward research and EBP were reported. Attitudes were predicted by exposure to research and EBP practice during graduate training and the clinical fellowship year (CFY). Clinical experience and opinions of colleagues were used to guide decision making more frequently than research studies or clinical practice guidelines. Only exposure to research and EBP during the CFY predicted use of evidence-based resources. Respondents reported a decline in exposure to research and EBP as they moved from graduate training into the CFY. A lack of time was perceived as a barrier to EBP.
170 citations (Crossref) [2023-10-31] Place: United States Zipoli, Richard P Jr. Southern Connecticut State University, New Haven, USA. ecrpz@aol.com
Keywords: *Attitude of Health Personnel; *Data Collection/sn [Statistics & Numerical Data]; *Evidence-Based Medicine; *Health Knowledge; Attitudes; Practice; *Speech-Language Pathology/st [Standards]; Clinical fellowship; Evidence-based practice; Humans; Practice issues; Research; Speech-Language Pathology/sn [Statistics & Numerical Data]; Speech-language pathology; Surveys and Questionnaires; United States; dept.cmd

Educating and training caregivers of persons with aphasia - Purdy, Mary; Hindenlang, Jane (Aphasiology, 2005)
Background: Because communication deficits caused by aphasia affect both persons with aphasia and their communication partners, most speech-language pathologists are aware of the importance of client and caregiver education. To maximise the effectiveness of their communicative interactions, training should be conducted for both the aphasic clients and their caregivers. Training conducted in group environments offers peer support through shared learning experiences and joint problem solving. Aims: The purpose of this study was to explore the benefits of a caregiver education and training programme in improving communication between caregivers and their aphasic partners using didactic and experiential approaches in a group setting. Methods & procedures: Ten caregivers and their aphasic partners, ranging from 4 to 130 months post-stroke, participated in a 12-week group training and education programme. Information about stroke and aphasia was provided in a didactic format, and facilitative communication strategies were discussed and practised using Kolb's (1984) experiential learning cycle model. The experiential learning cycle involved drawing on concrete experiences, engaging in reflective observation and abstract conceptualisation, and practising what was learned through active experimentation. Outcomes & results: Analysis of communicative performance on transactional and interactional tasks demonstrated increased communicative success. Responses on a questionnaire indicated that participants had a better understanding of aphasia and were more confident using facilitating strategies. Conclusions: Group education and training for caregivers and their aphasic partners can be beneficial, even after the couple has been living with aphasia for a number of years. Having an opportunity to practise, observe, and reflect on their performances facilitated participants' learning, and there were observed and reported positive alterations in interactions. © 2005 Psychology Press Ltd.
45 citations (Crossref) [2023-10-31] Citation Key Alias: pop00096 tex.type: [object Object]
Keywords: adult; aged; aphasia; article; caregiver; cerebrovascular accident; clinical article; cognition; dept.cmd; disease severity; education program; experience; female; group therapy; health education; human; information dissemination; interpersonal communication; learning; male; medical education; patient education; peer-reviewed; problem solving; questionnaire; self concept; social support; task performance

Perception and Production of Prosody by Speakers with Autism Spectrum Disorders. - Paul, Rhea; Augustyn, Amy; Klin, Ami; Volkmar, Fred R (Journal of Autism and Developmental Disorders, 2005)
Speakers with autism spectrum disorders (ASD) show difficulties in suprasegmental aspects of speech production, or prosody, those aspects of speech that accompany words and sentences and create what is commonly called "tone of voice." However, little is known about the perception of prosody, or about the specific aspects of prosodic production that result in the perception of "oddness." The present study examined the perception and production of a range of specific prosodic elements in an experimental protocol involving natural speech among speakers with ASD between 14 and 21 years of age, in comparison with a typical control group. Results revealed ceiling effects limiting interpretation of findings for some aspects of prosody. However, there were significant between-group differences in aspects of stress perception and production. The implications of these findings for understanding prosodic deficits is speakers with autism spectrum disorders, and for future research in this area, are discussed.
257 citations (Crossref) [2023-10-31] Place: United States Paul, Rhea. Southern Connecticut State University, USA. rhea.paul@yale.edu
Keywords: *Autistic Disorder/co [Complications]; *Language Disorders/et [Etiology]; *Perceptual Disorders/et [Etiology]; *Phonetics; *Speech Disorders/et [Etiology]; *Speech Perception; Adolescent; Adult; Autism; Autistic Disorder; Humans; Language; Language Disorders; Language Disorders/di [Diagnosis]; Language Tests; Male; Perceptual Disorders; Perceptual Disorders/di [Diagnosis]; Phonetics; Prosody; Speech Discrimination Tests; Speech Disorders; Speech Disorders/di [Diagnosis]; Speech Perception; Speech Production Measurement; article; autism; child; clinical article; clinical protocol; controlled study; correlation analysis; dept.cmd; human; intelligence quotient; intermethod comparison; language; medical assessment; peer-reviewed; perception; priority journal; prosody; reliability; scoring system; speech; speech disorder; statistical significance; stress; task performance

Communication quality indicators: A survey of connecticut group home managers - Desimone, Evelyn A; Cascella, Paul W (Journal of Developmental and Physical Disabilities, 2005)
Thirty-one Connecticut group home managers responded to a 23-statement survey adapted from the Communications Supports Checklist for Programs Serving Individuals with Severe Disabilities (CSC; McCarthy et al., 1998, Paul H. Brookes, Baltimore, MD.). Results indicated that group home managers had very favorable opinions about the implementation of communication quality indicators in their group homes, and the degree of a resident's intellectual disability was not a factor in communication supports implementation. Three communication quality indicators were rated especially high: program philosophy, protection of communication rights, and assessment. Environmental support for communication was rated less favorably. Follow-up interviews with seven group home managers found that they especially valued direct care staff who understood a resident's idiosyncratic communication (e.g., response sensitivity). Managers also relied on team process for referral for ongoing speech-language consultation. Results from the surveys and interviews indicated that augmentative communication applications occurred less often than other quality communication indicators.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-506-921-999-336 tex.type: [object Object]
Keywords: Communication supports; Group home; Severe disabilities; dept.cmd; peer-reviewed

Gin (gaps-in-noise) test performance in subjects with confirmed central auditory nervous system involvement - Musiek, Frank E; Shinn, Jennifer B; Jirsa, Robert E; Bamiou, Doriseva; Baran, Jane A; Zaida, Elena (Ear and Hearing, 2005)
OBJECTIVE: The purpose of the present study was to investigate the value of a new gap detection procedure called Gaps-In-Noise (GIN) for assessment of temporal resolution in a clinical population. DESIGN: The test consists of 0 to 3 silent intervals ranging from 2 to 20 msec embedded in 6-sec segments of white noise. The location, number, and duration of the gaps per noise segment vary throughout the test for a total of 60 gaps presented in each of four lists. The GIN procedure was administered to 50 normal-hearing listeners (group I) and 18 subjects with confirmed neurological involvement of the central auditory nervous system (group II). RESULTS: Results showed mean approximated gap detection thresholds of 4.8 msec for the left ear and 4.9 msec for the right ear for group I. In comparison, results for group II demonstrated a statistically significant increase in gap detection thresholds, with approximated thresholds of 7.8 msec and 8.5 msec being noted for the left and right ears, respectively. Significant mean differences were also observed in the overall performance scores (i.e., the identification of the presence of the gaps within the noise segments) of the two groups of subjects. Finally, psychometric functions, although similar for short and long duration gaps, were highly different for gaps in the 4- to 10-msec range for the two groups. CONCLUSIONS: A variety of psychoacoustic procedures are available to assess temporal resolution; however, the clinical use of these procedures is minimal at best. Results of the present study show that the GIN test holds promise as a clinically useful tool in the assessment of temporal resolution in the clinical arena. Copyright © 2005 by Lippincott Williams & Wilkins.
235 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-315-028-506-509 tex.type: [object Object]
Keywords: Adolescent; Adult; Aged; Aneurysm; Auditory Diseases; Central; Auditory Threshold; Case-Control Studies; Cerebrovascular Accident; Electrophysiology; Evoked Potentials; Auditory; Female; Humans; Male; Middle Aged; Noise; Perceptual Masking; Reaction Time; Reproducibility of Results; Stroke; adolescent; adrenoleukodystrophy; adult; article; auditory nervous system; brain artery aneurysm; clinical article; controlled study; dept.cmd; false positive result; female; gaps in noise test; hearing; hemispheric dominance; human; learning disorder; male; noise; pitch; psychometry; psychophysics; pure tone audiometry; receiver operating characteristic; stroke; temporal summation; test retest reliability; white noise

Brief Report: Relations between Prosodic Performance and Communication and Socialization Ratings in High Functioning Speakers with Autism Spectrum Disorders. - Paul, Rhea; Shriberg, Lawrence; McSweeny, Jane; Cicchetti, Domenic; Klin, Ami; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2005)
Shriberg et al. [ Shriberg, L. et al. (2001). Journal of Speech, Language and Hearing Research, 44, 1097-1115] described prosody-voice features of 30 high functioning speakers with autistic spectrum disorder (ASD) compared to age-matched control speakers. The present study reports additional information on the speakers with ASD, including associations among prosody-voice variables and ratings of communication social abilities. Results suggest that the inappropriate sentential stress and hypernasality previously identified in some of these speakers is related to communication/sociability ratings. These findings and associated trends are interpreted to indicate important links between prosodic performance and social and communicative competence. They suggest the need for careful assessment of inappropriate prosody and voice features in speakers with ASD, and for effective intervention programs aimed at reducing the stigmatization of individuals with these conditions., (C) Plenum Publishing Corporation 2005. All Rights Reserved.
131 citations (Crossref) [2023-10-31] Place: (C) Plenum Publishing Corporation 2005. All Rights Reserved.
Keywords: Adolescent; Adult; Asperger syndrome; Autism; Autistic Disorder; Communication; Female; Humans; Male; Middle Aged; Prosody; Severity of Illness Index; Socialization; Speech; Speech Production Measurement; Voice Quality; adolescent; adult; article; autism; child; clinical article; communication; communication skill; controlled study; dept.cmd; female; hospitalization; human; human experiment; interpersonal communication; linguistics; male; middle aged; nasal speech; peer-reviewed; priority journal; prosody; social adaptation; social psychology; socialization; speech; speech analysis; speech disorder; verbal communication; voice

Autism in a 15-month-old child - Klin, A; Chawarska, K; Paul, R; Rubin, E; Morgan, T; Wiesner, L; Volkmar, F (American Journal of Psychiatry, 2004)
38 citations (Crossref) [2023-10-31] tex.eissn: 1535-7228 tex.researcherid-numbers: Morgan, Tom/C-3478-2012 tex.unique-id: ISI:000224768400007
Keywords: dept.cmd

Discharge Practices in the University Clinical Setting - McNamara, Kevin M.; Hindenlang, Jane; Cascella, Paul W. (Contemporary Issues in Communication Science and Disorders, 2004)
This study investigated the degree to which clinic directors rated the influence of American Speech-Language-Hearing Association (ASHA) discharge criteria and organizational factors on client discharge in the university setting. Results found that university clinic directors regarded ASHA's client-centered criteria to more strongly influence client discharge practices than did organizational factors. In fact, organizational factors (e.e., fee structure, resources, scheduling, disorder characteristics) were revealed to have little to no influence on discharge practices. Results have implications for the pre-professional education of student clinicians in the university clinic and how student clinicians are oriented to discharge practices across a variety of clinical settings.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/193-563-257-057-896, mcnamaraDischargePracticesUniversity2004, pop00252
Keywords: dept.cmd

Pediatricians' opinions about otitis media and speech-language-hearing development - Sonnenschein, Esther; Cascella, Paul W (Journal of Communication Disorders, 2004)
Twenty-five pediatricians responded to a confidential survey about their opinions on the relationship between otitis media and children's speech-language-hearing status. Results found that pediatricians did not necessarily agree that otitis media has an impact on speech-language-hearing development. Pediatricians reported that an early otitis media onset (birth to age 2) affects speech-language development, but they also reported that parents and daycare environments could mitigate any otitis media effect. Pediatricians reported a possible otitis media impact on hearing status, but they did not necessarily agree that an otitis media history required referral for audiological testing. Clinical implications are discussed for collaboration among pediatricians, speech-language pathologists, and audiologists. Learning outcomes: (1) The reader will become familiar with pediatricians' opinions about the impact of otitis media on speech-language development. (2) The reader will become familiar with strategies to support interdisciplinary collaboration between pediatricians, speech-language pathologists, and audiologists. (C) 2004 Elsevier Inc. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-899-901-685-768 tex.type: [object Object]
Keywords: *Attitude to Health; *Hearing Disorders/ep [Epidemiology]; *Language Disorders/ep [Epidemiology]; *Otitis Media/ep [Epidemiology]; *Pediatrics; *Speech Disorders/ep [Epidemiology]; Child; Humans; Medical practices; Otitis media; Pediatricians; Speech-language development; dept.cmd; health survey; hearing; human; language development; medical practice; otitis media; pediatrician; questionnaire; review; speech development; thinking

Receptive communication abilities among adults with significant intellectual disability - Cascella, Paul W (Journal of Intellectual & Developmental Disability, 2004)
This study measured the receptive communication skills of 14 adults with significant intellectual disability living in community group homes in Connecticut. Group home staff members rated the 14 participants using it 14-item rating scale sensitive to the adult living situation. These individuals appeared to have relatively stronger skills for comprehension of single-step in-context directions and the ability to recognise that particular tangible objects represented certain daily routines. These individuals were relatively, weak in identifying,familiar people in photographs and common objects in magazines. Among these participants, persons with profound intellectual disability mere rated to hate lower receptive communication skills than persons with severe intellectual disability. Clinical implications are discussed for human service providers and education professionals.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-482-068-114-825 tex.type: [object Object]
Keywords: Down syndrome; adult; anxiety disorder; article; clinical article; depression; dept.cmd; developmental disorder; disability; disease severity; female; hearing loss; human; interpersonal communication; male; mental disease; psychosis; scoring system; seizure

Knowledge of autism spectrum disorders among connecticut school speech-language pathologists. - Cascella, Paul W; Colella, Catherine S (Focus on Autism and Other Developmental Disabilities, 2004)
This study utilized a rating scale and random sampling of Connecticut school speech—language pathologists about their preprofessional education and current knoWledge of autism spectrum disorders (ASD). The participants had a minimal amount of preprofessional academic or clinical preparation in ASD, and no differences Were found in hoW speech—language pathologists Were trained over the past 30 years. School speech—language pathologists reported relatively stronger knoWledge of the general behavioral and communication characteristics associated With ASD and less knoWledge of educational assessment and intervention formats. Given the prevalence of schoolchildren With ASD, speech—language pathology graduate programs need to enhance their preprofessional curricula to provide school-based speech—language pathologists With specific training to meet the communication needs presented by children With ASD. © 2004, Sage Publications. All rights reserved.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/100-419-323-620-14X tex.type: [object Object]
Keywords: dept.cmd

A collaborative preservice program in AT and AAC - Kennedy, Marianne; Shiller, Barbara (Perspectives on Issues in Higher Education, 2004)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-792-885-749-368 tex.type: [object Object]
Keywords: dept.cmd

Supervision: clinic directors of the northeast council of educational programs in communication sciences and disorders: the power of the collective voice - Lefkowitz, Nancy; Mcnamara, Kevin M; Bartlett, Susan E M (Perspectives on Administration and Supervision, 2004)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-990-390-755-729 tex.type: [object Object]
Keywords: dept.cmd

Adaptive behavior in autism and pervasive developmental disorder-not otherwise specified: Microanalysis of scores on the vineland adaptive behavior scales - Paul, R.; Miles, S.; Cicchetti, D.; Sparrow, S.; Klin, A.; Volkmar, F.; Coflin, M.; Booker, S. (Journal of Autism and Developmental Disorders, 2004)
The purpose of this study is to provide a microanalysis of differences in adaptive functioning seen between well-matched groups of school-aged children with autism and those diagnosed as having Pervasive Developmental Disorder-Not Otherwise Specified, all of whom functioned in the mild to moderate range of intellectual impairment. Findings indicate that the major area of difference between children with autism and those with Pervasive Developmental Disorder-Not Otherwise Specified, was expressive communication; specifically, the use of elaborations in syntax and morphology and in pragmatic use of language to convey and to seek information in discourse. Linear discriminant function analysis revealed that scores on just three of these expressive communication item sets correctly identified subjects in the two diagnostic categories with 80% overall accuracy. Implications of these findings for both diagnosis and intervention with children with Autism Spectrum Disorders will be discussed.
70 citations (Crossref) [2023-10-31]
Keywords: Activities of Daily Living; Adaptation; Psychological; Adaptive behavior; Autism; Autistic Disorder; Child; Child Development Disorders; Pervasive; Child; Preschool; Communication; Discriminant Analysis; Expressive language; Female; Humans; Personality Tests; Pervasive Developmental Disorders; Social Behavior; Socialization; adaptive behavior; article; autism; brain function; child; clinical article; comparative study; controlled study; dept.cmd; developmental disorder; diagnostic accuracy; diagnostic approach route; female; functional anatomy; human; intellectual impairment; interpersonal communication; language; linear system; male; microanalysis; peer-reviewed; priority journal; rating scale; scoring system; socialization; treatment indication

Promoting social communication in high functioning individuals with autistic spectrum disorders - Paul, Rhea (Child and Adolescent Psychiatric Clinics of North America, 2003)
This article reviews a range of social communication interventions that have been developed for students with autism at the preschool, school age, and adolescent level. Adult-mediated and peer-mediated methods that use highly structured, child-centered, and hybrid methods are examined. Programs that provide information on generalization and maintenance are identified. A set of recommendations for programs that would seem to be most appropriate for students with Asperger syndrome is presented.
69 citations (Crossref) [2023-10-31] Citation Key Alias: pop00024 tex.type: [object Object]
Keywords: *Asperger Syndrome/th [Therapy]; *Autistic Disorder/th [Therapy]; *Intelligence; *Social Behavior; Adolescent; Asperger Syndrome/di [Diagnosis]; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autistic Disorder/di [Diagnosis]; Autistic Disorder/px [Psychology]; Behavior Therapy; Child; Child; Preschool; Humans; Peer Group; Play and Playthings; Social Adjustment; adolescent; adult; autism; child; child psychiatry; dept.cmd; human; interpersonal communication; peer-reviewed; priority journal; review; school; social adaptation; social interaction; training; verbal communication

Management of children with APDs - Jirsa, Robert E (The Hearing journal, 2003)
The management of children with auditory processing disorders requires a multifaceted approach involving audiologists, speech-language pathologists, and educators. We are still at the genesis of our understanding of APDs.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-523-801-354-557 tex.type: [object Object]
Keywords: accuracy; association; audiology; auditory discrimination; auditory nervous system; auditory stimulation; auditory system examination; auditory system function; child; child behavior; child care; computer program; dept.cmd; frequency modulation; health care planning; hearing disorder; human; interpersonal communication; medical specialist; note; school; sensory system electrophysiology; signal noise ratio; signal processing; task performance; technology; writing

Clinical issues: Asperger Syndrome: the role of speech-language pathologists in schools - Paul, Rhea; Sutherland, Dean (Perspectives on Language Learning and Education, 2003)
5 citations (Crossref) [2023-10-31] Citation Key Alias: pop00102 tex.type: [object Object]
Keywords: dept.cmd

Methods for studying language production - Paul, R (Contemporary Psychology-Apa Review of Books, 2002)
1 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000175025300025
Keywords: dept.cmd

Speech and prosody characteristics of adolescents and adults with high-functioning autism and asperger syndrome - Shriberg, Lawrence D.; Paul, Rhea; McSweeny, Jane L.; Klin, Ami; Cohen, Donald J.; Volkmar, Fred R. (Journal of Speech Language and Hearing Research, 2001)
Speech and prosody-voice profiles for 15 male speakers with High-Functioning Autism (HFA) and 15 male speakers with Asperger syndrome (AS) were compared to one another and to profiles for 53 typically developing male speakers in the same 10- to 50-years age range. Compared to the typically developing speakers, significantly more participants in both the HFA and AS groups had residual articulation distortion errors, uncodable utterances due to discourse constraints, and utterances coded as inappropriate in the domains of phrasing, stress, and resonance. Speakers with AS were significantly more voluble than speakers with HFA, but otherwise there were few statistically significant differences between the two groups of speakers with pervasive developmental disorders. Discussion focuses on perceptual-motor and social sources of differences in the prosody-voice findings for individuals with Pervasive Developmental Disorders as compared with findings for typical speakers, including comment on the grammatical, pragmatic, and affective aspects of prosody.
362 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.cmd

Recovery of communication skills following intracerebral hemorrhage: A case study - Purdy, MH (Journal of Medical Speech-Language Pathology, 2001)
Numerous variables contribute to the ultimate recovery of communication skills following neurological damage. This report provides a review of the literature pertaining to prognostic indicators and chronicles the recovery of communication skills in a 48-year-old man who sustained a left intracerebral hemorrhage over a 29-month period.
tex.unique-id: ISI:000171100000007
Keywords: adult; article; brain hemorrhage; case report; communication disorder; dept.cmd; human; male; priority journal; prognosis; skill; speech rehabilitation; treatment outcome; ⛔ No DOI found

Psycholinguistic models of speech development and their application to clinical practice - Baker, Elise; Croot, Karen; Mcleod, Sharynne; Paul, Rhea (Journal of Speech Language and Hearing Research, 2001)
This article presents an introduction to psycholinguistic models of speech development. Two specific types of models are addressed: box-and-arrow models and connectionist or neural network models. We review some historical and some current models and discuss recent applications of such models to the management of speech impairment in children. We suggest that there are two ways in which a psycholinguistic approach can influence clinical practice: by directly supplementing a speech-language pathologist's repertoire of assessment and treatment approaches and by offering a new way to conceptualize speech impairment in children.
39 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-530-998-324-060 tex.type: [object Object]
Keywords: Assessment; Brain; Child Language; Child; Preschool; Connectionist models; Humans; Impairment; Language Disorders; Neural Networks (Computer); Psycholinguistic models; Psycholinguistics; Speech; Speech development; Verbal Learning; article; artificial neural network; brain; dept.cmd; human; language development; language disability; learning; linguistics; pathophysiology; preschool child; speech

TBI knowledge and pragmatic assessment among Connecticut school speech-language pathologists - McGrane, S.A.; Cascella, P.W. (Brain Injury, 2000)
School-based speech-language pathologists from Connecticut responded to a random survey which had a twofold purpose, (1) to replicate a previous conclusion that clinicians' specific experience with traumatic brain injury (TBI) influences their knowledge of this subject, and (2) to explore the topic of pragmatic assessment and whether it is also influenced by specific TBI experience. Results indicate that Connecticut school clinicians favourably regard both their own knowledge of TBI and the contemporary issue of pragmatic assessment. Connecticut clinicians also report a relatively low degree of prior TBI training and clinical experience. Clinicians' degree of TBI training and clinical experience did not appear directly related to their reported competence in TBI knowledge and pragmatic assessment.
10 citations (Crossref) [2023-10-31]
Keywords: *Brain Injuries/di [Diagnosis]; *Professional Competence; *Self-Assessment; *Speech-Language Pathology/ed [Education]; Adult; Connecticut; Female; Humans; Male; Middle Aged; Schools; Surveys and Questionnaires; Workforce; article; brain injury; competence; dept.cmd; education; experience; functional assessment; human; linguistics; normal human

Book Review: Stuttering and related disorders of fluency, third edition, edward g. conture, richard f. curlee (eds.). thieme medical publishers, inc., new york, NY (2007), 372 pp., hardback - Felsenfeld, Susan (Journal of Fluency Disorders, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-778-443-037-132 tex.type: [object Object]
Keywords: book.review; dept.cmd

Fundamental frequency and gender identification in standard esophageal and tracheoesophageal speakers. - Bellandese, Mary H (Journal of Communication Disorders, 2009)
UNLABELLED: The purpose of this study was to determine if there was a relationship between fundamental frequency (Fo) and gender identification in standard esophageal (ES) or tracheoesophageal (TE) speakers. Twenty-three male and 20 female ES and TE speakers participated in this study. Recordings of these speakers reading the Rainbow Passage were played to 48 listeners who indicated perceived gender in a forced choice format. Fo was determined using PC-AUDED [Boston University (1991). Using PC-AUDED, Audio-editor and analyses program for the study of periodic segments. Boston: Boston University]. Seventy-nine percent of the speakers were identified correctly for gender. No significant difference was found between the number of male and female or TE and ES speakers identified correctly. A significant correlation was found between Fo and correct gender identification for the female speakers only. Results suggest that Fo plays a part in gender identification for female SE and TE speakers, however, other factors may also be important cues for gender identification in these speakers., LEARNING OUTCOMES: As a result of this activity, the participant will be able to: (1) describe the relationship between Fo and gender identification for male and female standard esophageal (SE) and tracheoesophageal (TE) speakers (2) discuss other variables that may influence gender identification in SE and TE speakers.
3 citations (Crossref) [2023-10-31] Place: United States Bellandese, Mary H. Southern Connecticut State University, New Haven, CT 06515-1355, USA. bellandesem1@southernct.edu
Keywords: *Sex Characteristics; *Speech Acoustics; *Speech Perception; *Speech; Esophageal/px [Psychology]; *Trachea; Adult; Aged; Aged; 80 and over; Female; Humans; Male; Middle Aged; Sex Characteristics; Sound Spectrography; Speech Acoustics; Speech Perception; Speech; Esophageal; Task Performance and Analysis; Trachea; Young Adult; dept.cmd

Conversational Behaviors in Youth with High-functioning ASD and Asperger Syndrome. - Paul, Rhea; Orlovski, Stephanie; Marcinko, Hillary; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2009)
Twenty-nine youth with autism spectrum disorders and 26 with typical development between 12 and 18 years of age were engaged in structured interviews (ADOS). The interviews were videotaped and rated for atypical conversational behaviors by trained raters, using the Pragmatic Rating Scale (Landa et al. Psychol Med 22:245-254, 1992). The ASD group was divided into AS and HFA/PDD-NOS subgroups. Significant differences were found among groups on approximately one-third of the PRS items. These items involved primarily the management of topics and information, reciprocity, intonation, and gaze management. The only differences to reach significance between the AS and HFA/PDD-NOS group were a greater tendency for overly formal speech on the part of the AS group, and more difficulty with gaze management on the part of the group with HFA/PDD-NOS. The implications of these findings for understanding and treating conversational deficits in ASD are discussed., (C) Plenum Publishing Corporation 2009. All Rights Reserved.
173 citations (Crossref) [2023-10-31] Place: (C) Plenum Publishing Corporation 2009. All Rights Reserved.
Keywords: *Asperger Syndrome/di [Diagnosis]; *Autistic Disorder/di [Diagnosis]; *Interpersonal Relations; *Verbal Behavior; Adolescent; Asperger Syndrome; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autism; Autistic Disorder; Autistic Disorder/px [Psychology]; Child; Conversation; Female; Humans; Intelligence; Interpersonal Relations; Keywords; Language Development Disorders; Language Development Disorders/di [Diagnosis]; Language Development Disorders/px [Psychology]; Male; Pragmatics; Pragmatics Conversation; Speech Acoustics; Speech Intelligibility; Verbal Behavior; Vocabulary; article; autism; behavior; clinical article; controlled study; conversation; dept.cmd; human; juvenile; peer-reviewed; priority journal; rating scale; structured interview; videotape

Self-regulatory problem behaviors in 5-Year old twins with stuttering and high normal nonfluency - Felsenfeld, S.; Van Beijsterveldt, C. E. M.; Boomsma, D. I. (Behavior Genetics, 2008)
tex.organization: Behav Genet Assoc tex.unique-id: ISI:000260539000060 38th Annual Meeting of the Behavior-Genetics-Association, Louisville, KY, JUN 28, 2008
Keywords: dept.cmd; ⛔ No DOI found

Language outcomes of toddlers with autism spectrum disorders: A two year follow-up - Paul, Rhea; Chawarska, Katarzyna; Cicchetti, Domenic; Volkmar, Fred (Autism Research, 2008)
Thirty-seven children 15-25 months of age received clinical diagnoses of autism spectrum disorder (ASD) and were re-evaluated two years later. All subjects were judged to have retained a diagnosis of ASD at the follow-up evaluation. Communication scores for the group as a whole during the first visit were significantly lower than nonverbal IQ. However, by the second visit, verbal and nonverbal scores were no longer significantly different. The group was divided into two subgroups, based on expressive language (EL) outcome at the second visit. The two groups were similar in the second year of life in terms of expressive communication skills and autistic symptoms, except for a trend toward more stereotypic and repetitive behavior in the worse outcome group. By the second visit, however, the groups differed significantly on all standard measures of expression and reception, as well as on autistic symptomotology and nonverbal IQ. When assessed during their second year, children who ended up in the better outcome group showed higher average nonverbal cognitive level, receptive language (RL) scores, number of sounds and words produced, use of symbolic play schemes, and response to joint attention bids. Regression analysis revealed that the variables for which significant differences between the two outcome groups in their second year of life were found provided significant prediction of EL outcome at age four. Stepwise regression identified RL and presence of stereotypic and repetitive at the first visit as significantly associated with EL outcome. Implications of these findings for early identification and intervention are discussed.
90 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000270031600004
Keywords: Autism; Autistic Disorder; Child; Preschool; Communication; Follow-Up Studies; Humans; Infant; Language; Language Disorders; Language Tests; Language Therapy; Observer Variation; Questionnaires; Severity of Illness Index; Toddlers; article; autism; dept.cmd; follow up; hospitalization; human; infant; interpersonal communication; language disability; language test; observer variation; preschool child; questionnaire; speech therapy

Production of syllable stress in speakers with autism spectrum disorders - Paul, Rhea; Bianchi, Nancy; Augustyn, Amy; Klin, Ami; Volkmar, Fred R. (Research in Autism Spectrum Disorders, 2008)
This paper reports a study of the ability to reproduce stress in a nonsense syllable imitation task by adolescent speakers with autism spectrum disorders (ASD), as compared to typically developing (TD) age-mates. Results are reported for both raters' judgments of the subjects' stress production, as well as acoustic measures of pitch range and duration during stressed and unstressed syllable production. Results reveal small but significant differences between speakers with ASD and typical speakers in both perceptual ratings of stress and instrumental measures of duration of syllables. The implications of these findings for understanding prosodic deficits in ASD are discussed. (C) 2007 Elsevier Ltd. All fights reserved.
47 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/160-980-016-423-349 tex.unique-id: [object Object]
Keywords: Autism; Prosody; Syllable stress; acoustics; adolescent; adult; article; autism; clinical article; controlled study; dept.cmd; feedback system; female; human; intelligence quotient; male; mental task; motor coordination; pitch; priority journal; school child; speech articulation; speech perception; task performance

Auditory processing disorder - Paul, Rhea (Journal of Autism and Developmental Disorders, 2008)
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-593-662-752-574 tex.type: [object Object]
Keywords: *Auditory Perceptual Disorders/co [Complications]; *Auditory Perceptual Disorders/di [Diagnosis]; *Autistic Disorder/co [Complications]; *Autistic Disorder/di [Diagnosis]; Auditory Perceptual Disorders; Autistic Disorder; Child; Cognition Disorders; Cognition Disorders/co [Complications]; Humans; Male; Speech Perception; audiologist; auditory processing disorder; autism; brain; central nervous system; dept.cmd; ear; editorial; hearing disorder; hearing test; peer-reviewed; priority journal; signal transduction; social interaction; sound transmission; speech

Performance of bilingual speakers on the English and Spanish versions of the Hearing in Noise Test (HINT). - Weiss, Deborah; Dempsey, James J (Journal of the American Academy of Audiology, 2008)
This study compared the performance of bilingual participants on the English and Spanish versions of the Hearing in Noise Test (HINT). The participants were divided into an early bilingual (EB) group and a late bilingual (LB) group based on age of second-language acquisition. All participants acquired Spanish as their first language (L1) and English as a second language (L2). Care was taken to ensure that all participants demonstrated at least a "good competence level" for self-rated speaking, understanding, reading, and writing skills in both English and Spanish. Results revealed superior performance on the Spanish HINT versus the English HINT in both quiet and in noise for both groups of participants. Significant differences in performance were noted for the EB versus the LB participants. A number of possible explanations for superior performance in L1 are provided, and implications for educating students in their L2 are discussed.
54 citations (Crossref) [2023-10-31] Place: United States Weiss, Deborah. Department of Communication Disorders, Southern Connecticut State University, 501 Crescent Street, Davis Hall, New Haven, CT 06515, USA. weissd1@southernct.edu
Keywords: *Language Tests; *Multilingualism; *Speech Perception/ph [Physiology]; *Verbal Learning/ph [Physiology]; Adolescent; Adult; Age Factors; Bilingual; Child; English as a second language; Female; Hearing; Hearing in Noise Test; Humans; Language Tests; Linguistic competence; Male; Multilingualism; Noise; Regression Analysis; Speech Perception; Speech recognition in noise; Speech recognition in quiet; Students; United States; Verbal Learning; adolescent; adult; article; auditory threshold; bilingualism; controlled study; dept.cmd; education; female; human; language ability; learning environment; linguistics; male; normal human; peer-reviewed; priority journal; school child; self report; signal noise ratio; speech and language assessment; speech intelligibility; speech perception

Eliciting a distal gesture via dynamic assessment among students with moderate to severe intellectual disability - McLaughlin, Katherine; Cascella, Paul W. (Communication Disorders Quarterly, 2008)
This study attempted to elicit distal gestures within dynamic assessment structured sampling events from six children with moderate to severe intellectual disability (ages 8-13). Using four communication temptations and a least-to-most prompting hierarchy across three sessions, three participants who had both pre-symbolic and preintentional communication demonstrated an initial distal gesture, often in response to a choice making temptation. Clinical implications are discussed with regard to the utility of dynamic assessment structured sampling activities. © 2008, SAGE Publications. All rights reserved.
8 citations (Crossref) [2023-10-31] Citation Key Alias: pop00153 tex.type: [object Object]
Keywords: dept.cmd

Differentiating ASD from DLD in toddlers - Paul, Rhea; Chawarska, Katyrzyna; Volkmar, Fred R (Perspectives on Language Learning and Education, 2008)
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-582-369-786-82X tex.type: [object Object]
Keywords: dept.cmd

Heritability of Stuttering and Non-Fluency in 5-Year-Old Dutch Twins. - van Beijsterveldt, C.; Felsenfeld, S.; Boomsma, D. (Behav Genet, 2008)
Place: (C) Plenum Publishing Corporation 2008. All Rights Reserved.
Keywords: dept.cmd; ❓ Multiple DOI

“Listen my children and you shall hear”: Auditory preferences in toddlers with autism spectrum disorders - Paul, Rhea; Chawarska, Katarzyna; Fowler, Carol; Cicchetti, Domenic; Volkmar, Fred (Journal of Speech Language and Hearing Research, 2007)
Purpose: This study tests the hypothesis that toddlers with autism spectrum disorders (ASD) will show differences from contrast groups in preferences for attending to speech. Method: This study examined auditory preferences in toddlers with ASD and matched groups of (a) typical age-mates, (b) age-mates with nonautistic developmental disabilities, and (c) younger children matched for language age. The experimental procedure measured time spent oriented to auditory stimuli that were created to exemplify language patterns that had been studied in typically developing infants. Results: Findings suggest that toddlers with ASD show a reduced preference for child-directed speech, compared with typical age-mates, but few differences from children with nonautistic developmental disorders. Correlational analysis revealed that time spent listening to child-directed speech by children with ASD was related to their concurrent receptive language ability as well as to receptive language abilities 1 year later. This relationship did not hold for the other groups. Conclusion: The present study supports the hypothesis that children with ASD perform differently from typical peers in auditory preference paradigms and that performance in these tasks is related to concurrent and later language development.
75 citations (Crossref) [2023-10-31] tex.eissn: 1558-9102 tex.unique-id: ISI:000250280300017
Keywords: *Attention; *Autistic Disorder/px [Psychology]; *Child Behavior; *Choice Behavior; *Infant Behavior; *Speech Perception; Attention; Auditory comprehension; Autism spectrum disorders; Autistic Disorder; Child Behavior; Child; Preschool; Choice Behavior; Comprehension; Female; Humans; Infant; Infant Behavior; Language Development; Language comprehension; Male; Speech Perception; article; auditory stimulation; auditory system; autism; controlled study; correlation analysis; dept.cmd; developmental disorder; female; human; language; language ability; language development; major clinical study; male; peer group; preschool child; speech; time; toddler

Increasing stroke patients' success in self-medication programs using an interdisciplinary cognitive rehabilitation approach. - Purdy, Mary (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2007)
Rehabilitation programs strive to help patients become more independent in all aspects of daily living. Therefore, management of a patient's healthcare requirements should be an integral part of the rehabilitation program, including management of medications. Some rehabilitation programs implement self-medication programs (SMP); however, patients with cognitive deficits are often excluded. This study explored whether patients with cognitive deficits due to stroke could successfully complete an SMP using an interdisciplinary cognitive rehabilitation approach. Twenty-seven stroke patients and 36 debilitated patients with cognitive deficits participated in an SMP. A nurse and a pharmacist educated patients on their medications, and a speech-language pathologist provided cognitive rehabilitation to the stroke patients, which incorporated information from the SMP. Eighty-one percent of the stroke patients successfully completed the SMP, compared to 36% of the debilitated patients. Thus, an interdisciplinary approach to medication management for cognitively impaired stroke patients holds promise.
3 citations (Crossref) [2023-10-31] Place: United States Purdy, Mary. Southern Connecticut State University, Department of Communication Disorders, USA. purdym1@southernct.edu
Keywords: *Cognition Disorders/rh [Rehabilitation]; *Patient Care Team/og [Organization & Administration]; *Patient Education as Topic/og [Organization & Administration]; *Self Administration; *Stroke/co [Complications]; Aged; Analysis of Variance; Case-Control Studies; Cerebrovascular Accident; Cognition Disorders; Cognition Disorders/et [Etiology]; Cognition Disorders/px [Psychology]; Curriculum; Humans; Length of Stay; Length of Stay/sn [Statistics & Numerical Data]; MLCS; MLOWN; Middle Aged; Needs Assessment; Nursing Assessment; Nursing Evaluation Research; Patient Care Team; Patient Education; Pharmacy Service; Hospital; Pharmacy Service; Hospital/og [Organization & Administration]; Problem Solving; Program Evaluation; Rehabilitation Nursing; Rehabilitation Nursing/og [Organization & Administration]; Self Administration; Self Administration/mt [Methods]; Self Administration/px [Psychology]; Severity of Illness Index; Speech-Language Pathology; Speech-Language Pathology/og [Organization & Administration]; Treatment Outcome; aged; analysis of variance; article; case control study; cerebrovascular accident; cognitive defect; curriculum; dept.cmd; drug self administration; evaluation; health care quality; hospital pharmacy; hospitalization; human; length of stay; methodology; middle aged; needs assessment; nursing assessment; nursing evaluation research; organization and management; patient care; patient education; problem solving; psychological aspect; rehabilitation nursing; speech disorder; statistics; treatment outcome

Ratings of communication competence by siblings of persons with Down syndrome - Smith, Sarah E.; Cascella, Paul W. (Education and Training in Developmental Disabilities, 2007)
This study surveyed 25 siblings of persons with Down Syndrome to gain an ecological perspective about important communication competence indicators. Siblings favorably described persons with Down Syndrome as “effective” and “good” communicators who “communicate to potential. “ Siblings regarded social communication skills as especially important, i.e., being able to communicate without fear, being able to express wants, needs, opinions, and feelings, being able to ask questions, and alerting partners to communication breakdowns. Siblings also regarded language comprehension as an important skill. Favorable descriptive labels were often applied to adult-aged persons with mild ID and normal hearing. Clinical implications are discussed focused on functional communication planning and implementation that takes into account the perspectives of family members, teachers, and rehabilitation personnel.
Citation Key Alias: lens.org/178-041-737-828-555 tex.unique-id: [object Object]
Keywords: dept.cmd; ⛔ No DOI found

Autism spectrum disorder in the second year: stability and change in syndrome expression - Chawarska, Katarzyna; Klin, Ami; Paul, Rhea; Volkmar, Fred (Journal of Child Psychology and Psychiatry, 2007)
Objectives: Increasing numbers of young children referred for a differential diagnosis of autism spectrum disorders (ASD) necessitates better understanding of the early syndrome expression and the utility of the existing state-of-the art diagnostic methods in this population. Method: Out of 31 infants under the age of 2 years referred for a differential diagnosis, 19 were diagnosed with autism, and 9 with pervasive developmental disorder-not otherwise specified (PDD- NOS) when reassessed at 3 years. We examined 1) the symptoms of ASD in the second year and changes in the syndrome expression by the age of three; 2) relationship between expert-assigned clinical diagnosis and diagnostic classification based on Autism Diagnostic Observation Schedule-Generic (ADOS-G) and Autism Diagnostic Interview-Revised (ADI-R) in the second year; 3) the relationship between direct observation and parental report of ASD symptoms. Results: Symptoms of autism and PDD- NOS in the second year were pronounced and stability of the clinical diagnosis was high. The agreement between clinician-assigned autism but not PDD- NOS diagnosis and the ADOS-G was high. However, sensitivity of the ADI-R diagnostic classification of autism was poor. Comparison of concurrent parental report and direct observation revealed discrepancies in severity ratings of key dyadic social behaviors. Changes in communication reflected acquisition of language accompanied by the emergence of unusual language characteristics. Symptoms of social dysfunction were relatively stable over time, and so was the severity of stereotyped behaviors. Conclusions: The study provides support for stability of clinical diagnosis and syndrome expression in the second year and highlights advantages and limitations of the ADI-R and ADOS-G for diagnosing and documenting symptoms of ASD in infants.
245 citations (Crossref) [2023-10-31] START/CPEA Network Meeting, Washington, DC, 2004 Citation Key Alias: lens.org/007-431-320-363-097 tex.unique-id: [object Object]
Keywords: ADI-R; ADOS-G; ASD; Assessment; Autism; Autistic Disorder; Child; Preschool; Communication; Diagnosis; Differential; Disease Progression; Early Diagnosis; Earlydiagnosis; Female; Humans; Infant; Infants; Interpersonal Relations; Language Development Disorders; Longitudinal studies; Male; PDD-NOS; Questionnaires; Social Behavior; Stereotyped Behavior; Toddlers; article; assessment; autism; communication disorder; controlled study; dept.cmd; differential diagnosis; disease severity; early diagnosis; female; follow up; human; infants; language disability; longitudinal studies; longitudinal study; male; observational study; patient referral; pervasive developmental disorder not otherwise specified; play; preschool child; psychologic assessment; psychological rating scale; sensitivity analysis; social behavior; social disability; social interaction; stereotypy; symptomatology; toddlers

Parental recognition of developmental problems in toddlers with autism spectrum disorders - Chawarska, Katarzyna; Paul, Rhea; Klin, Ami; Hannigen, Sarah; Dichtel, Laura E.; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2007)
Symptoms of Autism Spectrum Disorders (ASD) begin to manifest during the first 2 years; there is limited evidence regarding type and timing of symptom onset. We examined factors related to parental age of recognition (AOR) of early abnormalities and the association between AOR and diagnosis and levels of functioning at 2 and 4 years in 75 toddlers with ASD. Results suggest significant differences between autism and PDD-NOS in the AOR and type of first concerns. Early social and motor delays as well as maternal age was associated with AOR. Later AOR was associated with poorer social-communicative and nonverbal cognitive functioning at 2 and 4. The findings are discussed in a context of identifying distinct developmental trajectories within the autism spectrum.
175 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-540-720-732-679 tex.unique-id: [object Object]
Keywords: Age Factors; Age of recognition; Autism; Autistic Disorder; Child; Preschool; Cognition Disorders; Developmental Disabilities; Early Diagnosis; Female; Follow-Up Studies; Humans; Infants; Male; Mass Screening; PDD-NOS; Parents; Recognition (Psychology); Regression; Severity of Illness Index; Social Behavior; article; autism; clinical feature; dept.cmd; developmental disorder; early diagnosis; functional assessment; human; major clinical study; maternal age; motor performance; nonverbal communication; parental attitude; peer-reviewed; preschool child; priority journal; social interaction

Focused stimulation for a child with autism spectrum disorder: A treatment study - Grela, Bernard G.; McLaughlin, Kathryn S. (Journal of Autism and Developmental Disorders, 2006)
This study explored the use of focused stimulation as an intervention technique for a three-year-old boy diagnosed with autism spectrum disorder (ASD). His parents were trained to use focused stimulation to facilitate comprehension of what is x doing question forms. Responses to question probes were collected at both pre- and post-treatment intervals. At the beginning of the study, the child did not respond correctly to any of the target questions. Following intervention, the child made significant gains towards the target goal, but little change towards a control goal used for comparison. These findings provide preliminary support for the usefulness of focused stimulation as an intervention strategy for at least some children with ASD.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-268-412-392-746 tex.unique-id: [object Object]
Keywords: Attention; Autism spectrum disorder; Autistic Disorder; Child; Preschool; Comprehension; Early Intervention (Education); Focused stimulation; Follow-Up Studies; Generalization (Psychology); Humans; Imagination; Imitative Behavior; Language Development Disorders; Language Therapy; Male; Natural language procedures; Parent intervention; Play and Playthings; Speech Perception; article; autism; brain function; case report; child parent relation; cognitive therapy; comprehension; dept.cmd; focused stimulation; human; information processing; language; language development; male; peer-reviewed; preschool child; priority journal; questionnaire; statistical significance

Prediction of strategy usage by adults with aphasia - Purdy, Mary; Koch, Amy (Aphasiology, 2006)
Background: Management of aphasia often focuses on training augmentative communication strategies such as communication books, computerised systems, gestures, writing, or drawing. Although many individuals are able to acquire a targeted skill in a structured format, many do not successfully use the trained skill in more functional situations. Training alternative communication strategies can be a time-consuming project; thus, it would be beneficial if speech-language pathologists could predict, a priori, how a patient may respond to this type of treatment approach. It has been hypothesised that use of augmentative communication strategies requires executive functioning, specifically cognitive flexibility, which may be impaired following brain damage. Therefore, assessment of cognitive flexibility may help clinicians determine which persons with aphasia would most likely benefit from training of augmentative communication strategies. Aims: The purpose of this study was to develop a measure of cognitive flexibility and to determine whether this measure predicted strategy usage during a functional communication task. Methods and Procedures: A novel scoring system for the Communicative Abilities in Daily Living (CADL) was developed to capture the degree of participants' cognitive flexibility. This score was correlated with the Wisconsin Card Sorting Test (WCST), to determine the validity of the scoring system. The CADL cognitive flexibility score was then correlated with performance on a referential communication task. A multiple regression analysis was conducted with severity of aphasia as an additional predictor variable. Outcomes and Results: There was a significant correlation between the cognitive flexibility score from the CADL and the WCST, confirming the validity of the scoring system as a measure of cognitive flexibility. Results of the regression analysis demonstrated a significant relationship between the cognitive flexibility score and strategy usage on a functional communication task. This relationship remained significant when the overall severity of aphasia was added to the regression analysis, suggesting that cognitive flexibility is a stronger predictor of strategy usage than severity of aphasia. These results may provide clinicians insight into which individuals would benefit most from the training of compensatory strategies, leading to the development of more appropriate goals and treatment methods.
50 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/105-511-629-177-420 tex.type: [object Object]
Keywords: adult; aged; aphasia; apraxia; article; clinical article; cognition; comorbidity; computer assisted tomography; control strategy; coping behavior; dept.cmd; disease association; disease severity; drawing; facilitated communication; fluency disorder; gesture; human; peer-reviewed; prediction; verbal communication; writing

Standardised speech-language tests and students with intellectual disability: a review of normative data. - Cascella, Paul W (Journal of intellectual & developmental disability, 2006)
Background: Before a school speech-language pathologist (SLP) utilises a standardised speech-language test with a student with intellectual disability (ID), the clinician should carefully consider the purpose of the test and whether the test includes students with ID in the normative group. Method: This project reviewed 49 tests published between 1994 and 2004 and their applicability to students with ID. Results: Students with mild ID were included in the norm group for 23 of the tests, but no tests included students with more significant ID. Separate norms for students with mild ID were included in 15 tests, but none met Salvia & Ysseldyke's (1995) suggested requirement that at least 100 students be included to represent a specific subgroup. A majority of the tests assessed receptive and expressive vocabulary, syntax, and grammar but no recent test measured a student's pragmatic communication. Conclusions: Clinicians are encouraged to supplement standardised tests with non-standardised procedures to document students' pragmatic, social, and functional communication abilities. © 2006 Australasian Society for the Study of Intellectual Disability Inc.
11 citations (Crossref) [2023-10-31] Place: England Cascella, Paul W. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. cascellap1@southernct.edu
Keywords: *Intellectual Disability; *Language Disorders/di [Diagnosis]; *Language Disorders/ep [Epidemiology]; *Language Tests; *Speech Disorders/di [Diagnosis]; *Speech Disorders/ep [Epidemiology]; Humans; Intellectual disability; Language Disorders; Language Tests; Language test; Mental Retardation; Reference Values; Severity of Illness Index; Speech Disorders; Speech test; Student; adolescent; article; child; dept.cmd; diagnostic value; grammar; human; interpersonal communication; linguistics; major clinical study; mental deficiency; social adaptation; social aspect; social status; speech analysis; speech language pathologist; student; systematic review

An electrophysiologic approach to APD - Jirsa, Robert E; Musiek, Frank E (The Hearing journal, 2006)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-302-398-869-950 tex.type: [object Object]
Keywords: audiology; auditory cortex; auditory discrimination; auditory processing disorder; auditory stimulation; auditory threshold; dept.cmd; electrophysiology; evaluation; hearing acuity; human; hypoacusis; language; neurophysiology; short survey; speech perception; temporal lobe; voice onset time

Management of dysphagia following stroke: A case study - Purdy, Mary (Perspectives on Neurophysiology and Neurogenic Speech and Language Disorders, 2006)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-718-625-526-839 tex.type: [object Object]
Keywords: dept.cmd